Constructing hierarchical Ti3SiC2 layer and carbon nanotubes on SiC fibers for enhanced electromagnetic wave absorption. Issue 5 (1st March 2023) - Zou, Yangjun; Huang, Xiaozhong; Fan, Benhui; Tang, Zipeng; Zhou, Junhong; Peng, Panjun; Liu, Xuancheng; Zhu, Jingbo; Liu, Yu; Yue, Jianling
Abstract: To enhance the absorption performance of silicon carbide fiber (SiCf ), hybrid fibers with a double shell structure (Ti3 SiC2 and carbon nanotubes (CNTs)) on the SiCf (CNT@Ti3 SiC2 @SiCf ) were successfully synthesized by the combination of molten salt method and floating catalytic chemical vapor deposition. A series of 10% weight fraction fibers reinforced paraffin samples was prepared to study the double coating influences on the electromagnetic wave (EMW) absorption performances. Coated by Ti3 SiC2 and CNTs, the dielectric permittivity of hybrid fibers could be modulated in a quite wide range. The CNT@Ti3 SiC2 @SiCf with a thickness of 3.8 mm showed a minimum reflection loss value of −53 dB at 6.57 GHz, and the CNT@Ti3 SiC2 @SiCf with a thickness of 2.5 mm presented a wide effective absorption bandwidth of 5.6 GHz (from 9 to 14.6 GHz). The highly improved EMW absorption performance of CNT@Ti3 SiC2 @SiCf was attributed to the combination of conductive loss and dielectric loss aroused by interfaces. The excellent absorption performance provided the modified SiCf with a high potential in the application of EMW absorbers.